Imigração pelo mar - Santos, Túlio Vinícius Dias (2022)
Immigration, a phenomenon whose occurrence is ageless, can be understood as the voluntary or imposed movement of exit of an individual from a given State territory, wherein one is not a national, with the interest of establishing his centre of life in another State’s territory. For historical contingences, migration flows either are incentivated or governments decide to mitigate them or even try to prevent them from happening, which in practical terms is not factual. Anyway, irregular immigration is repelled in name of States’ Sovereignty towards their territories and their inherent right to include and exclude, to decide who shall be granted with the right of entrance and permanence as well as those who have no other option apart from compulsory expulsion. In the E.U. it would not differ; irregular immigration is a typical phenomenon which takes place by land as well as by sea. As to the former, border control in E.U. external frontiers are systematized and juridically well defined; as to the latter, immigration - which is as relevant as the other in International Law and whose dimensions are imesurable given that it happens in the sea, is not as well defined as when it takes place in land. Therefore, it is mandatory to observe the relation between irregular immigration in the sea, the ideal pathway for human trafficking, with the Law of the Sea, given the fact that since 2015 one verifies an increase of migration flows in the Mediterranean Sea. The present project intends to verify what are the implications that immigration could have towards the General Duty of Rescue (GDR) and above all, after the rescue, analyse the tension among State Sovereignty and the Non-refoulement principle. For it to occur States rely on their Sovereign Rights to the detriment of recognised international principles and human rights. As an answer to it, this work unites Jacques Derrida’s Hospitality Theory in order to consolidate a new theory amid the immigration in the E.U, with Hannah Arendt´s writings on refugees and stateless people. Furthermore, this text also intends to observe the concept of foreigner and how foreigners have been treated along History. All this to the best understanding of the contingencies which have molded the way Nation State relates with its non-nationals.